Low temperature heat capacities of boracites. Issue 1 (31st August 2016) - Castellanos-Guzman, A. G.; Soto García, V. M.; Bayarjargal, L.; Haussühl, E.; Winkler, B.
ABSTRACT: Low temperature specific heat measurements have been performed on Mn3 B7 O13 Br and Fe3 B7 O13 I boracites. As expected, we observe mag-netic ordering at low temperatures. The Neel temperature of the Fe3 B7 O13 I (Fe-I) boracite (31.4 K) differs significantly from the Neel temperature of Fe3 B7 O13 Cl (Fe-Cl) boracite (11.8 K, Schnelle et al., 1999). The same is true for the Mn3 B7 O13 Br (Mn-Br) boracite, where we observe a transition at 25.9 K, while Schnelle et al. (1999) observed the transition in Mn3 B7 O13 Cl (Mn-Cl) boracite at 11 K.